IDIOMS IN TEACHING CULTURE - Jalilova Dildora Sheralievna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. The article deals with the issues of the role of idioms in teaching culture and their importance in language teaching. Idioms are an important part of language, since they are used to convey our feelings in more concise and effective way. Language as a zone of communication has literal meaning is the direct reference of words or sentences to object, figurative sense is used for giving invective portraiture or distinctive effect. Such a meaning characterizes notions like metaphors, proverbs and idioms. Idioms, as means of non-literal language, have a vital extent use in functional language. In this study, an attempt is made to look at the use of idioms and why need to teach idioms in teaching culture. The present paper aims at how idioms are connected to one’s feelings, how one can develop communicative skills effectively through idioms.